Investigating Particle Size-Flux Relationships and the Biological Pump Across a Range of Plankton Ecosystem States From Coastal to Oligotrophic - Fender, Christian K.; Kelly, Thomas B.; Guidi, Lionel; Ohman, Mark D.; Smith, Matthew C.; Stukel, Michael R. (Frontiers in Marine Science, 2019)
Sinking particles transport organic carbon produced in the surface ocean to the ocean interior, leading to net storage of atmospheric CO2 in the deep ocean. The rapid growth of in situ imaging technology has the potential to revolutionize our understanding of particle flux attenuation in the ocean; however, estimating particle flux from particle size and abundance (measured directly by in situ cameras) is challenging. Sinking rates are dependent on several factors, including particle excess density and porosity, which vary based on particle origin and type. Additionally, particle characteristics are transformed while sinking. We compare optically-measured particle size spectra profiles (Underwater Vision Profiler 5, UVP) with contemporaneous measurements of particle flux made using sediment traps and 234Th:238U disequilibrium on six process cruises from the California Current Ecosystem (CCE) LTER Program. These measurements allow us to assess the efficacy of using size-flux relationships to estimate fluxes from optical particle size measurements. We find that previously published parameterizations that estimate carbon flux from UVP profiles are a poor fit to direct flux measurements in the CCE. This discrepancy is found to result primarily from the important role of fecal pellets in particle flux. These pellets are primarily in a size range (i.e., 100 – 400 µm) that is not well-resolved as images by the UVP due to the resolution of the sensor. We develop a new, CCE-optimized algorithm for estimating carbon flux from UVP data in the southern California Current (Flux = ∑_(i=1)^x▒〖n_i A〖d_i〗^B ∆d_i 〗), with A = 13.45, B = 1.35, d = particle diameter (mm) and Flux in units of mg C m-2 d-1. We caution, however, that increased accuracy in flux estimates derived from optical instruments will require devices with greater resolution, the ability to differentiate fecal pellets from low porosity marine snow aggregates, and improved sampling of rapidly sinking fecal pellets. We also find that the particle size-flux relationships may be different within the euphotic zone than in the shallow twilight zone and hypothesize that the changing nature of sinking particles with depth must be considered when investigating the remineralization length scale of sinking particles in the ocean.